Individual versus team heart rate variability responsiveness analyses in a national soccer team during training camps - Muñoz-López, A.; Naranjo-Orellana, J. (Scientific Reports, 2020)
Heart rate variability (HRV) analyses can be performed using group or individual changes. Individual changes could be of potential interest during training camps for national soccer teams. The purpose of this study was to compare whether analysis of individual daily HRV could detect changes in cardiac autonomic responses during training camps for national soccer teams. During two different training camps, 34 professional soccer players were monitored daily over 9 days, using heart rate monitors. Players were divided into First Eleven (those who participated in the main squad) or Reserves. Daily HRV was individually analyzed using a day-to-day method or a baseline (days prior to first match) method, using the smallest worthwhile change and the typical error in the estimate to establish a trivial (random change) zone. Group changes were also analyzed using an ANOVA one-way repeated measures test. Players` responsiveness was classified as High-, Low- or Non-response depending on individual changes. Both analyses showed substantial daily individual changes after playing a soccer match, regardless of the group. However, group changes showed that only First Eleven players had significant changes after playing a soccer match. In conclusion, individual daily HRV analyses are useful in detecting individual changes in professional soccer players.